Wearable Smartwatch Facilitated Remote Health Management for Patients Undergoing Transcatheter Aortic Valve Replacement - Xianbao Liu; Jiaqi Fan; Yuchao Guo; Hanyi Dai; Jianguo Xu; Lihan Wang; Po Hu; Xinping Lin; Cheng Li; Dao Zhou; Huajun Li; Jian’an Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background In the recent decades, the development of novel digital health technologies enables doctors to monitor ECG and vital signs remotely. But the data on applying the noninvasive wearable smartwatch on patients with transcatheter aortic valve replacement (TAVR) are unknown. Methods and Results We performed a prospective, observational cohort study to evaluate the feasibility of a novel, virtual, and remote health care strategy for patients with TAVR discharged to home with smart wearable devices. A total of 100 consecutive patients with severe aortic stenosis who underwent elective transfemoral TAVR were enrolled and received the Huawei smartwatch at least 1 day before TAVR. Vital signs, including heart rate, rhythm, oxygen saturation, and activity, were continuously recorded. Single‐lead ECG was recorded twice per day in the week following TAVR discharge and at least 2 days a week for the subsequent month after TAVR discharge. A designated heart team member provided remote health care with the data from the smartwatch when the patient had a need. Thirty‐eight cardiac events were reported in 34 patients after discharge, with most of the events (76.0%) detected and confirmed by the smartwatch. Six patients were advised and readmitted to the hospital for arrhythmia events detected by the smartwatch, of whom 4 patients received pacemaker implantation. The remaining 28 (82.4%) patients received telemedicine monitoring instead of face‐to‐face clinical visits, and 3 of them received new medication treatment under the online guidance of doctors. New‐onset left branch bundle block was found in 48 patients, with transient characteristics, and recovered spontaneously in 30 patients, and new‐onset atrial fibrillation was detected in 4 patients. There were no significant differences in the average weekly heart rates or the ratio of abnormal or low oxygen saturation when compared with the baseline. The average daily steps increased over time significantly (baseline, 870±1353 steps; first week, 1986±2406 steps; second week, 2707±2716 steps; third week, 3059±3036 steps; fourth week, 3678±3485 steps, P<0.001). Conclusions Smartwatches can facilitate remote health care for patients discharged to home after undergoing TAVR and enable a novel remote follow‐up strategy. The majority of cardiac clinical events that occurred within 30‐day follow‐up were detected by the smartwatch, mainly because of the record of conduction abnormality. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT04454177.